2021
DOI: 10.3390/app11041791
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Topography Sensing by Osteoblasts: An Update

Abstract: Bone is a specialized tissue formed by different cell types and a multiscale, complex mineralized matrix. The architecture and the surface chemistry of this microenvironment can be factors of considerable influence on cell biology, and can affect cell proliferation, commitment to differentiation, gene expression, matrix production and/or composition. It has been shown that osteoblasts encounter natural motifs in vivo, with various topographies (shapes, sizes, organization), and that cell cultures on flat surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 123 publications
1
12
0
Order By: Relevance
“…245−247 The phenotypic response of MSCs to substrate topography is a result of the fine balance between cellular tension, focal adhesion development, and nuclear deformation elicited directly by the topographical geometries. 248,249 This is particularly relevant to MSC osteogenesis due to the wealth of knowledge that links these mechanotransductive factors to fate choice and osteogenesis. A common finding is that microscale topographies (ranging from 1 to 10 μm) significantly enhance osteogenesis by facilitating the translocation of mechanosensitive transcription factors such as YAP and RUNX2 to the nuclear compartment.…”
Section: Neural Differentiationmentioning
confidence: 99%
“…245−247 The phenotypic response of MSCs to substrate topography is a result of the fine balance between cellular tension, focal adhesion development, and nuclear deformation elicited directly by the topographical geometries. 248,249 This is particularly relevant to MSC osteogenesis due to the wealth of knowledge that links these mechanotransductive factors to fate choice and osteogenesis. A common finding is that microscale topographies (ranging from 1 to 10 μm) significantly enhance osteogenesis by facilitating the translocation of mechanosensitive transcription factors such as YAP and RUNX2 to the nuclear compartment.…”
Section: Neural Differentiationmentioning
confidence: 99%
“…Superficial roughness measured around 1.5 μm have been considered by several authors as the best topographical condition for bone cell adhesion and successful osseointegration, due to an improved connection between the substrate and the cellular membrane when compared to smooth or highly-rougher surfaces [ 49 , 50 ]. The anodized surface proposed here achieved a roughness around 1.37 μm (Sa roughness parameter), corroborating to be quite similar to the gold standard for bone cells [ 49 , 50 ]. This specific roughness was achieved by the combination of firstly an acid-attack treatment aiming to add roughness to the smooth Ti surface, followed by an anodization process aiming to create a nanotopography.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophilic rough surface enhanced the expression level of osteogenesis related genes and significantly increased the expression of several Wnt ligands such as Wnt3a, Wnt5a, and the Wnt receptors of the Frizzled family in Wnt signaling pathway ( Galli et al, 2010 ; Donos et al, 2011 ; Li et al, 2017 ). Wnt proteins interact with frizzled-LRP surface receptors such that the down stream effector β -catenin is increasingly translocated to the nucleus ( Li et al, 2017 ), while at the same time inhibiting the complex that degrades β -catenin, namely AXIN1 ( Hutchings et al, 2020 ; Rougerie et al, 2021 ). Under these conditions, the increased signaling through Wnt/β-catenin signaling pathway is associated with the expression of calcification and osteogenic markers.…”
Section: Signaling Pathways Of Interface Morphology On Osteogenesismentioning
confidence: 99%
“…Importantly, the exogenous addition of Wnt5a and Wnt5a knock-down experiments demonstrated that the integrin upregulation was Wnt-dependent ( Olivares-Navarrete et al, 2011 ), suggesting a mutually reinforcing crosstalk between integrin adhesions and Wnt signalling ( Barlian and Vanya, 2022 ). Integrin regulates differentiation through the Wnt pathway, and Wnt increases the expression of integrin, resulting in further regulation of osteogenic differentiation ( Sun et al, 2018 ; Rougerie et al, 2021 ).…”
Section: Signaling Pathways Of Interface Morphology On Osteogenesismentioning
confidence: 99%